Holy Ghost feasts in Tambor de Mina cult houses: Modes of articulations. (September 2019) - Leal, João
This article is centred on the diverse modes of articulation between Tambor de Mina – the African-Brazilian religion prevalent among the Black population of São Luís (the state capital of Maranhão, Brazil) – and Holy Ghost feasts – a Catholic feast that is the most important public celebration in Tambor de Mina cult houses. My focus is on the creative processes associated with these diverse modes of articulation. I argue that these processes are connected, on one hand, to the wider politics of boundary management between religious genres that each cult house adopts and, on the other hand, to different politics of display and containment centred on the visibility of Tambor de Mina in the public space. The article is both a contribution to recent anthropological debates on creativity and to discussions on processes of interface between different religious genres in African-Brazilian religions.